Karakteristik Massa Air Berdasarkan Sebaran Suhu dan Klorofil-a di Perairan Teluk Ambon - Randy Simaela; Domey L. Moniharapon; Taufuniringsi Kesaulya; Irma Kesaulya (Jurnal Sumberdaya Akuatik Indopasifik, 2022)
Ambon Bay consists of the inner Ambon Bay (IAB) and the outer Ambon Bay (OAB) and they are separated by the shallow sill (12 m) Galala-Rumah Tiga. The topography of the bay makes it unique and causes the exchange of water mass between those two parts of the bay does not follow the daily tidal cycle. The aim of this study was to analyze the vertical and horizontal temperature and chlorophyll-a distribution in order to know the water circulation in Ambon Bay. This study was carried out during the monsoon, in November 2018. The CTD was used to measure in situ temperature and chlorophyll-a concentration. The data were analyzed by using Surfer and ODV programs. The results show that the temperature of the surface water (0-5 m) of Ambon Bay was 29.2℃. In depth 15-40 m, temperature was different between the IAB (27.7-28.2℃) and OAB (29,2-28.7℃). Chlorophyll-a concentration was found higher in the IAB than in OAB in all depths. In the depth >12 m, chlorophyll-a in the IAB was 1 mg/m3 compared to its concentration in OAB only 0.3 mg/m3. As a conclusion, the sill in Ambon bay causes unique circulation of water mass between IAB and OAB based on the analysis of temperature and chlorophyll-a concentration distribution.